Physical activity towards health and fitness: combative sports - Cabanilla, Joel S.; Calingayan, Jones Q.; Carino, Leonardo L.; Kitongan, Vivian Grace L.; Marquez, Shiela Marie M.; Pascual, Arsenio T.
Physical activity provides knowledge on health and fitness activities.
Includes bibliographical references.